HIV/AIDS and impoverishment : a study in Mpumalanga Province in South Africa - Khosa, Patricia (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Industrial Psychology))--University of Stellenbosch, 2009.